INDONESIA'S GLOBAL HEALTH DIPLOMACY IN THE TIME OF COVID-19 PANDEMIC - Asep Setiawan; Debbie Affianty; Nurul Fitralaila Tanjung (Universitas Nasional, 2022)
COVID-19, which has been sweeping the world since 2020 and has caused a high human toll, profoundly impacts almost all countries to focus on public health. Indonesia also felt the impact of COVID-19; therefore, it needs to participate in various activities in maintaining global health and seeking vaccines from the international world. This study aims to examine how Indonesia's global health diplomacy during the COVID-19 pandemic. The research used a qualitative method with data collection techniques through secondary data and interviews. The study found that Indonesia conducted global health diplomacy through multilateral channels to maintain global health governance and promote international efforts in dealing with the COVID-19 pandemic. Indonesia also uses global health diplomacy through multilateral and bilateral channels to gain access to vaccine provision. Indonesia's global health diplomacy was also conducted to obtain assistance in dealing with non-health problems, namely economic and social issues.